(untitled) (Marketing Jurnali, 2026)
This article scientifically analyzed the impact of inflation on the purchasing power of the population in Uzbekistan using a macroeconomic approach. The study evaluated the relationship between inflation dynamics, the consumer price index, real household income, and consumption expenditures based on official statistical data and reports from international organizations. It also systematically examined the effects of monetary policy, fiscal measures, and social protection mechanisms on price stability and household welfare. The findings demonstrated opportunities to maintain stable inflation, protect real incomes, strengthen social support mechanisms, and enhance macroeconomic stability. The study provided a reliable scientific basis for improving the effectiveness of economic policy and supporting sustainable household welfare.